The Childfree Phenomenon in Indonesia in Contemporary Islamic Studies: Study of Takhrij and Syarah Hadith - Nabila, Husna; Gumus, Fatih (Journal of Takhrij Al-Hadith, 2023)
This study aims to discuss the hadith about childfree. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about childfree in Imam Ahmad’s narration No. 12152. The results and discussion of this study indicate that the status of this hadith is of sahih quality which is maqbul ma’mul bih as an evidence. This study concludes that the Hadith narrated by Imam Ahmad No. 12152 is relevant to be used as a proof in answering the phenomenon of childfree as a form of contribution to contemporary Islamic studies.